HEALTH AND VOLUNTEERING - Silva Moreira Carvalho, Rayane Figueiredo (2021)
Introduction: A volunteer is an individual who dedicates part of his/her time to activities related to the society without any remuneration. There are several reasons to do that, such as personal values, self knowledge, self development, improvement of self esteem and relevant motivations to the society, besides personal altruism. Studies show a positive relationship between volunteering and health as a decrease in risk factors to cardiovascular diseases and to mortality risks, besides psychological and social well-being improvements. Objectives: Identify the reasons which motivate the volunteering and comprehend the reflection in the practice of the volunteering work in the health of the one who does it. Methods: Systematic review through carried out  search in a time cut of five years,  encompassing researches published from 2015 to 2020 and articles in a complete text format. The inclusion criterias were to select scientific articles which had information about the volunteer work relating it to the health of the one who practices it and the main reasons which drive individuals to dispose their time to such activities. On the other hand, the exclusion criterias were based on discarding bibliographic reviews and articles with more than five years of publication. Thus, 18 articles were elected. Topics to be addressed: Reasons to volunteering; Reflection of volunteering in health. Final considerations: Once we have seen the benefits for both the individual and his/her social context,  the volunteer work is a practice which must be stimulated due to its contribuition to both development.